Assessment of Asymptomatic Urinary Tract Infection and Susceptibility of Antimicrobials Agents and Resistant Patterns among Suspected Females Patients of Two Major Hospitals of Western Nepal: Assessment of Asymptomatic Urinary Tract Infection and Susceptibility of Antimicrobials Agents and Resistant Patterns among Suspected Females Patients of Two Major Hospitals of Western Nepal - Sharma, Dr. Suman (International Journal of Pharmaceutical & Biological Archive, 2019)
Urinary tract infection (UTI) is a common and serious health problem affecting many people each year around the world especially females. Therapy of UTI relies on the predictability of the agents causing UTI and knowledge of their antimicrobial susceptibility patterns. A retrospective cross-sectional study was conducted in two major hospitals of Western Nepal. Tools for data collection were a data collection form. A total of 400 patient’s file with suspected UTI were reviewed, out of which 173 (43.3%) of the suspected samples showed the presence of potential pathogens causing UTI. UTI was most prevalent in females of age group of 21–30 years. Escherichia coli was the predominant (65.1%) bacterial pathogen. Amikacin was found to be the most sensitive antimicrobial followed by nitrofurantoin and gentamicin. Ampicillin showed a higher percentage of resistant, compared to other antimicrobials. As drug resistance among bacterial pathogens is an evolving process, regular surveillance and monitoring are necessary to provide effective treatment of UTIs.